1996
DOI: 10.1111/j.1365-2982.1996.tb00241.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between intraluminal multiple electric impedance measurement and manometry in the human oesophagus

Abstract: Conventional oesophageal manometry and intraluminal electrical impedance measurement were simultaneously applied in eight healthy volunteers to study the effect of wet and semisolid bolus viscosities on oesophageal motility and bolus transit. Contraction front velocity measured by electrical impedance and manometry were identical for wet and semisolid swallows and highly associated. Bolus front velocity as measured by electrical impedance was significantly faster than contraction front velocity in both wet and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
39
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 15 publications
9
39
0
Order By: Relevance
“…Furthermore, an exact comparison between bolus movements throughout the esophagus detected by MII-pH, and the manometric pressure waves does not seem to be possible. This would be related to the fact that manometry can offer good information on both amplitude and peristaltic progression of esophageal contractions, but very little information either on bolus transit [15] or secondary peristalsis (not spontaneous but following swallow episodes). Second, based upon the small number of patients, it would seem that a lack of a proper power calculation cannot allow any meaningful conclusions with regard to outcome that should be confirmed in a larger number of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, an exact comparison between bolus movements throughout the esophagus detected by MII-pH, and the manometric pressure waves does not seem to be possible. This would be related to the fact that manometry can offer good information on both amplitude and peristaltic progression of esophageal contractions, but very little information either on bolus transit [15] or secondary peristalsis (not spontaneous but following swallow episodes). Second, based upon the small number of patients, it would seem that a lack of a proper power calculation cannot allow any meaningful conclusions with regard to outcome that should be confirmed in a larger number of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional oesophageal manometry and impedance monitoring were simultaneously applied in eight healthy volunteers (HV) to study the effect of bolus viscosity on oesophageal motility and bolus transit. 6 The results indicated that electrical impedance measurement is a reliable technique to detect oesophageal motility as well as to differentiate between transit of liquid and semisolid bolus consistencies.…”
Section: Bolus Transitmentioning
confidence: 97%
“…2,3,[5][6][7][8][9][10][11][12] Figure 2. Bolus passage along a neighbouring pair of electrodes yields a typical impedance tracing, including five phases: baseline impedance during resting stage of the oesophagus (phase 1); impedance rise caused by arrival and passage of an air volume ahead of the bolus (phase 2); impedance drop and recovery caused by arrival and passage of the bolus (phase 3); impedance rise caused by wall contraction associated with lumen occlusion (phase 4) and recovery of impedance signal to baseline level during transition to resting stage (phase 5).…”
Section: Validation Studiesmentioning
confidence: 99%
“…Multichannel intraluminal impedance combined with manometry can help distinguish rumination from regurgitation related to an incompetent antirefl ux barrier or another esophageal motor disease [23•]. For example, regurgitation of ingested food followed by remastication then swallowing appears on combined impedance-manometry as increased intragastric pressure by manometry with subsequent impedance changes consistent with regurgitation of food and [25]. As a result, efforts have focused on combining these techniques because they are largely complementary (Fig.…”
Section: Rumination and Belchingmentioning
confidence: 98%